Interdisciplinary Approach to the Dynamics of Islamic Family Law Practices in Indonesia, Malaysia, and Egypt - Muhammad Febri Eka Saputra; Sukriyani Sukriyani (USRATY : Journal of Islamic Family Law, 2025)
This study aims to explore the dynamics of Islamic family law practices in Indonesia, Malaysia, and Egypt through an interdisciplinary approach that integrates social, cultural, and jurisprudential perspectives. The research seeks to identify how these three dimensions interact in shaping the interpretation and implementation of Islamic family law across different national contexts. Methodologically, the study employs a comparative qualitative design, combining doctrinal analysis of statutory and jurisprudential sources with socio-legal observations of social practices and cultural norms in family-related disputes and policy implementation. Primary data from legal documents and court decisions are examined alongside secondary sources, including scholarly works and policy reports, to ensure a holistic and balanced understanding. The findings reveal significant variations: Indonesia reflects a pluralistic system where social realities, cultural expectations, and jurisprudential interpretations intersect between state law and religious courts; Malaysia illustrates how federal-state relations influence cultural identity and Islamic legal autonomy; and Egypt demonstrates the enduring impact of classical jurisprudence while gradually adapting to modern social and cultural changes. Despite these differences, all three contexts highlight the tension between tradition and modernity in regulating marriage, divorce, and inheritance. The study concludes that only by integrating social, cultural, and jurisprudential analyses can the complexities of Islamic family law be adequately understood, since purely doctrinal or sociological approaches risk oversimplification. Academically, the research contributes to comparative Islamic legal studies by offering a replicable model that foregrounds the social, cultural, and jurisprudential interplay in Muslim-majority contexts, thus advancing interdisciplinary inquiry beyond rhetorical claims toward substantive, evidence-based insights.